Changes in the rate of publicly financed knee arthroscopies: an analysis of data from the Norwegian patient registry from 2012 to 2016. Issue 6 (15th June 2018) - Holtedahl, Robin; Brox, Jens Ivar; Aune, Arne Kristian; Nguyen, Daniel; Risberg, May Arna; Tjomsland, Ole
Abstract : Objective: To examine rates of publicly financed knee arthroscopic surgery in Norway between 2012 and 2016. Design: Analysis of anonymised data from the National Patient Registry. Interventions: Beginning in 2012, South-Eastern Norway Regional Health Authority implemented administrative measures to bring down rates of knee arthroscopy. Similar measures were not introduced in the other three Regional Health Authorities. Main outcome measures: We analysed annual national rates of publicly financed knee arthroscopies in 2012 and 2016. We compared the rates in South-Eastern Norway Regional Health Authority with corresponding rates in the rest of the country. Variations by county, public hospital versus publicly reimbursed private hospital, gender and age were also assessed. Results: The overall annual rate of arthroscopic procedures declined by 33% from 2012 to 2016, from 310 to 207 per 100 000 inhabitants, respectively. Hospitals in South-Eastern Norway Regional Health Authority reported a 48% reduction, compared with mean 13% in the other three Regional Health Authorities. In public hospitals, rates decreased nationally by 42%, while rates in publicly reimbursed private hospitals increased by 12%. Rates in publicly reimbursed private hospitals decreased by 30% in South-Eastern Norway Regional Health Authority but increased by 63% in the other Regional Health Authorities. The proportion of patients ≥50 years (excluding meniscal repairs) in Norway was 54% in 2012 and fell to 46% in 2016. Average rates per county varied by a factor of 3:1. Conclusion: We report a marked overall reduction of knee arthroscopic procedures from 2012 to 2016 in publicly funded hospitals. The largest decrease was reported in South-Eastern Norway Regional Health Authority, and this coincides in time with implemented administrative measures. The results suggest that the trend of increasing rates of knee arthroscopies can be reversed through purposeful professional and administrative interventions.